Assessment of coal quality on the site “Uspenivska No 2” in Western Donbas based on the statistical analysis of its chemical and technological properties - Savchuk, V; Rudakov, D; Prykhodchenko, D (National Mining University, 2016)
Purpose. To conduct a comprehensive assessment of the coal seams’ quality on the site “Uspenivska No 2” in Lozivskyi coal-bearing area of the Western Donbas industrial district; establish their grade composition according to current standards, and find the main directions of their rational use. Methods. The research is based on the methods of analysis, synthesis, and statistical treatment of indices followed by the prognosis and refining of coal quality characteristics. Findings. We analyzed the reserves of fuel and energy resources of Ukraine and evaluated chemical and technological characteristics of coal seams for the site “Uspenivska No 2”. Statistical treatment of the data allowed to reveal the relationships between the quality indices and establish lateral and stratigraphic patterns. The grade composition has been specified and the ways of coal rational use have been considered. Originality. The distribution patterns of coal quality parameters have been established for the site “Uspenivska No 2” in Lozivskyi coal-bearing area of the Western Donbas by statistical analysis. In particular, statistical significance of the reduction in the vitrinite reflectance index and combustion heat, as well as the increase in volatiles output with increasing depth has been confirmed. Practical implications. Detailed statistical analysis of coal quality allowed giving recommendations on rational use and implementation of clean technologies of coal processing at the stage of geological exploration.

Цель. Всесторонняя оценка качества основных промышленных угольных пластов участка “Успеновский №2” Лозовского угленосного района Западного Донбасса, установление их марочного состава по действующим стандартам и определение основных направлений их рационального использования. Методика. Методической основой исследований является анализ, обобщение и статистическая обработка показателей с последующим прогнозом и выявлением особенностей качества угля. Результаты. Выполнен анализ запасов топливно-энергетических ресурсов Украины, дана химико-технологическая характеристика углей пластов участка “Успеновский №2”. Проведенная статистическая обработка данных позволила выявить зависимости между показателями качества, а также установить латеральные и стратиграфические закономерности. Уточен марочный состав и пути рационального использования угля. Научная новизна. Путем статистического анализа установлены закономерности распределения показателей качества углей для пластов участка “Успеновский №” Лозовского угленосного района Западного Донбасса, в частности, подтверждена статистическая значимость уменьшения показателя отражения витринита и теплоты сгорания, а также увеличения выхода летучих веществ с увеличением глубины. Практическая значимость. Детальный статистический анализ данных качества угля позволяет дать рекомендации по рациональному использованию и внедрению чистых технологий переработки угля еще на стадии геологоразведочных работ.

Мета. Оцінка якості основних промислових вугільних пластів ділянки “Успенівська №2” Лозівського вугленосного району Західного Донбасу, встановлення їх марочного складу за діючими стандартами та визначення основних напрямків раціонального використання. Методика. Методичною основою дослідження є проведення аналізу, узагальнення та статистичної обробки показників із подальшим прогнозом та виявленням особливостей якості вугілля. Результати. Виконано аналіз запасів паливно-енергетичних ресурсів України, надано хіміко-технологічну характеристику вугілля пластів ділянки “Успенівська №2”. Проведена статистична обробка даних, яка дозволила виявити залежності між показниками якості й встановити латеральні та стратиграфічні закономірності. Уточнено марочний склад і шляхи раціонального використання вугілля. Наукова новизна. Шляхом статистичного аналізу встановлено закономірності розподілу показників якості вугілля для пластів ділянки “Успенівська №2” Лозівського вугленосного району Західного Донбасу, зокрема, підтверджена статистична значимість зменшення показника відбиття вітриніту та теплоти згорання, а також збільшення виходу летючих речовин зі збільшенням глибини. Практична значимість. Детальний статистичний аналіз даних якості вугілля дозволяє надати рекомендації щодо раціонального використання та впровадження чистих технологій переробки вугілля ще на стадії геологорозвідувальних робіт.
Keywords: coal; chemical and technological parameters; ash content; sulfur content; combustion heat